Flexible Adult Acquired Flatfoot Deformity: Comparison Between Weight-Bearing and Non-Weight-Bearing Measurements Using Cone-Beam Computed Tomography. (20th September 2017) - de Cesar Netto, Cesar; Schon, Lew C.; Thawait, Gaurav K.; da Fonseca, Lucas Furtado; Chinanuvathana, Apisan; Zbijewski, Wojciech B.; Siewerdsen, Jeffrey H.; Demehri, Shadpour
Abstract : Background: The 3-dimensional nature of adult acquired flatfoot deformity can be challenging to characterize using radiographs. We tested the hypothesis that measurements on weight-bearing (WB) cone-beam computed tomography (CT) images were more useful for demonstrating the severity of the deformity than non-weight-bearing (NWB) measurements. Methods: We prospectively enrolled 12 men and 8 women (mean age, 52 years; range, 20 to 88 years) with flexible adult acquired flatfoot deformity. The subjects underwent cone-beam CT while standing (WB) and seated (NWB), and images were assessed in the sagittal, coronal, and axial planes by 3 independent observers who performed multiple measurements. Intraobserver and interobserver reliabilities were assessed with the Pearson or Spearman correlation and the intraclass correlation coefficient (ICC), respectively. Measurements were compared using paired Student t tests or Wilcoxon rank-sum tests. P < 0.05 was considered significant. Results: We found that overall the measurements had substantial intraobserver and interobserver reliability on both the NWB images (mean ICC, 0.80; range, 0.49 to 0.99) and the WB images (mean ICC, 0.81; range, 0.39 to 0.99). Eighteen of 19 measurements differed between WB and NWB cone-beam CT images, with more pronounced deformities on the WB images. The most reliable measurements, based on intraobserver and interobserver reliabilities and the difference between WB and NWB images, were the medial cuneiform-to-floor distance, which averaged 29 mm (95% confidence interval [CI] = 28 to 31 mm) on the NWB images and 18 mm (95% CI = 17 to 19 mm) on the WB images, and the forefoot arch angle (mean, 13° [95% CI = 12° to 15°] and 3.0° [95% CI = 1.4° to 4.6°], respectively) in the coronal view and the cuboid-to-floor distance (mean, 22 mm [95% CI = 21 to 23 mm] and 17 mm [95% CI = 16 to 18 mm], respectively) and the navicular-to-floor distance (mean, 38 mm [95% CI = 36 to 40 mm] and 23 mm [95% CI = 22 to 25 mm], respectively) in the sagittal view. Conclusions: Measurements analogous to traditional radiographic parameters of adult acquired flatfoot deformity are obtainable using high-resolution cone-beam CT. Compared with NWB images, WB images better demonstrated the severity of osseous derangement in patients with flexible adult acquired flatfoot deformity. Level of Evidence: DiagnosticLevel II . See Instructions for Authors for a complete description of levels of evidence.